VOLATILE COMPOUNDS’ CHARACTERIZATION OF N-HEXANE EXTRACTS OF TERASA’S FOREST HONEY - Aulia Winaldi; Alfian Noor; Firdaus Firdaus (Marina Chimica Acta, 2018)
This study aims to identify volatile compounds that are characteristic of the honey of Terasa village of Sinjai regency of South Sulawesi, volatile honey extracted with n-hexane solvent then identified by Gas Chromatography Mass Spectroscopy (GCMS) method. The results obtained 59 volatile compounds derived from honey are grouped into compounds namely hydrocarbons, aldehydes, ketones, alcohols, esters, bensenoid and carboxylic acids. Based on comparative results with other honey regions it is known that volatile compounds that become characteristic of honey Terasa village that is compound Tetrasilaoktana